2018
DOI: 10.21608/edj.2018.78396
|View full text |Cite
|
Sign up to set email alerts
|

Translucency Evaluation of Zirconia Lithium Silicate and Lithium Disilicate Glass Ceramic With Different Thicknesses Pre and Post Cementation

Abstract: OBJECTIVES:The aim of this study was to evaluate translucency of zirconia lithium silicate and lithium disilicate glass ceramic with different thicknesses, pre and post cementation. MATERIALS AND METHODS:A 120 Specimens of the current study were fabricated out of the two tested materials each counting N=60, A1 (translucent) shades of zirconia-reinforced lithium silicate glass ceramic (ZLS, Vita Suprinity, Vita Zahnfabrik, Germany) and A1(translucent) lithium disilicate glass ceramics (Rosetta SM, Korea). Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Comparison of simple main effects presented in table (3) showed that, When no thermal tempering was applied, IPS E.max press crowns showed statistically significant higher mean fracture resistance value than Celtra press crowns (p<0.001). While with thermal tempering 9% below pressing temperature; Celtra press crowns demonstrated statistically significant higher fracture resistance values than Emax press (p=0.010).…”
Section: -Fracture Resistance Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of simple main effects presented in table (3) showed that, When no thermal tempering was applied, IPS E.max press crowns showed statistically significant higher mean fracture resistance value than Celtra press crowns (p<0.001). While with thermal tempering 9% below pressing temperature; Celtra press crowns demonstrated statistically significant higher fracture resistance values than Emax press (p=0.010).…”
Section: -Fracture Resistance Resultsmentioning
confidence: 99%
“…Recently, novel ceramic materials have been developed in an effort to combine polycrystalline ceramics mechanical properties and glass ceramics' superior esthetics 2 . IPS E.max was launched in 2007 as an updated generation of lithium disilicate ceramics, with improved physical properties and excellent translucency using different firing processes 3 . Its microstructure contains 3 to 6 μm in length needle-shaped lithium disilicate crystals, approx.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of new brands share similar compositions in the same indication range. The substitution for lithium disilicate glass ceramic on the market is a zirconia-reinforced lithium silicate glass ceramic (LS1) (Celtra Duo, SironaDentsply, Bensheim, Germany) [ 22 , 23 , 24 , 25 ]. These ceramics are characterized by the same indication and similar characteristics; however, the procedural steps for digital dentistry usage (CAD/CAM) are not entirely given.…”
Section: Introductionmentioning
confidence: 99%